BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA KARYAWAN PT X - Miftah Septina Supriyadi Aziz; Sutarto Wijono (Jurnal Cakrawala Ilmiah, 2023)
Effective human resource management is a key focus for many organizations looking to gain a competitive edge. Previous studies have shown that employee performance has an impact on organizational culture, compensation, and employee motivation. This study aims to explore the influence of organizational culture on employee motivation. This is a quantitative study. The research questionnaire uses a Likert scale checklist. The population of this study is all employees of PT X, totaling 450 people. The results of the study show that organizational culture has a positive and significant effect on employee motivation. The implications of this study are that companies need to pay attention to their organizational culture in order to improve employee motivation.